Cirebon Regency’s National Commission for Child Protection’s role in handling sexual violence against children - Synthia Lustiana; Santi Sumarjo; Moriza Mega; Sanusi Sanusi; Ari Nurhaqi (Interdisciplinary Social Studies, 2024)
Sexual violence against children is a violation of human rights that has a long-term traumatic impact. The phenomenon of increasing cases of sexual violence against children has become a global problem that requires serious attention. This increase continues to occur in various regions, including Cirebon Regency. The role of the Regional Indonesian Child Protection Committee (KPAID) of Cirebon Regency in handling this case is very important. This study analyzes the role of KPAID Cirebon in overcoming sexual violence against children, identifies the factors that cause an increase in child sexual violence, and examines the role of KPAID Cirebon Regency in dealing with child sexual violence cases, focusing on prevention, case handling, and challenges faced. This study uses a qualitative method with a case study approach. Data was collected through in-depth interviews with the Chairman of the Cirebon Regency KPAID, the victim's family, and other related parties. The results of the study show that KPAID Cirebon Regency plays an active role in receiving reports, providing legal and psychological assistance and advocating to protect the rights of victims. However, KPAID faces challenges that affect its effectiveness in carrying out its role, such as limited resources, lack of public awareness and weak coordination between institutions. And this phenomenon continues to increase supported by many external and internal factors such as environmental factors and the victim's own family factors.